"Powerful Lessons" in Women's Sport: ESPN's Nine for IX Series. (December 2020) - Antunovic, Dunja; Linden, Andrew D.
In 2013, ESPN launched a series of documentaries to celebrate the 40th anniversary of Title IX. The Nine for IX documentaries tell stories of successful women in sport and tackle pertinent gender- and sex-related issues, promising to teach popular audiences about the untold histories of women's sport. Because of the series' place in ESPN's marketing efforts to reach women, we consider the series as ideological work through which women's sport history is constructed. Drawing on feminist sport scholarship, we argue that the Nine for IX films fall short of their promised socially conscious and educational potential. Instead of interrogating broader webs of power, the series overwhelmingly relies upon individualized, depoliticized, and postfeminist narratives that relegate efforts toward gender equality to the past. The series is, thus, a reflection of ESPN's larger problems with representations of women's sport.